The Relationship between Household Debt and Consumption Spending in South Africa - Nkala, Patience; Tsegaye, Asrat (Journal of Economics and Behavioral Studies, 2017)
Consumption has been and remains the main contributor to gross domestic product (GDP) growth in South Africa. Household debt on the other side has remained high over the years. These two economic indicators are a reflection of the well-being of an economy. This study thus examined the relationship between household debt and consumption spending, for the period between 1994 and 2013. The Johansen cointegration technique and the Vector error correction model (VECM) were utilised to test the long run and short run relationships between the variables. The Granger causality test was also employed to test the direction of causality between the variables. Results from this study have revealed that a relationship exists between household debt and consumption spending in South Africa and they have also showed that this relationship flows from household debt to consumption spending. The implications of these results are that consumption spending may be increased through other measures rather than through increasing debt. The study therefore recommends that policy makers avail more investment opportunities for households and to also create employment in a bid to increase the income of households which can then be used to increase household consumption rather than the use of debt.